Conjunctive cohesion in English language EU documents–A corpus-based analysis and its implications. - Trebits, Anna (English for Specific Purposes)
This paper reports the findings of a study which forms part of a larger-scale research project investigating the use of English in the documents of the European Union (EU). The documents of the EU show various features of texts written for legal, business and other specific purposes. Moreover, the translation services of the EU institutions often produce texts that exhibit features which in terms of textual organization neither link them to the source language nor to the target language of texts. The aim of the present corpus-based study is to describe one type of cohesion: the use of conjunctions in EU documents in order to uncover some of the textual organization patterns they show. Therefore, an EU English Corpus of approximately 200,000 running words was built using texts which represent the diverse fields of activities of the EU. The analysis compares the use of conjunctions in EU-related and general English texts using the database of the British National Corpus (BNC). The paper also illustrates some data-driven instructional activities that may be used in EFL/ESL classrooms when teaching English for EU purposes.